The Relationship Between Lifestyle and Attachment to God With Depression Mediated by Quality of Life Among Mothers of Children With Intellectual Disabilities - Mahasti Samadpour Javaheri; Sasan Bavi; Farzaneh Hooman (Gonabad University of Medical Sciences, 2022)
Background: Mothers often bear a heavy psychological burden in society because of their disabled children. As mothers often spend more time taking care of these children, they are exposed to different types of stress and mental disorders. The present study aims to investigate the relationship between lifestyle and attachment to God with depression with the mediating role of Quality of Life (QoL) in mothers of children with intellectual disabilities (IDs) in Tehran, Iran. Methods: This descriptive-correlational study was conducted using path analysis. The statistical population comprised all the mothers of children with IDs in Tehran, Iran in 2020. Among the study population, a total of 213 mothers were selected as the sample via convenience sampling. The research instruments included the Beck depression inventory-II (BDI-II), the attachment to God questionnaire, the lifestyle assessment inventory (LSI), and the World Health Organization quality of life questionnaire-short form (WHOQoL-BREF). The proposed model was evaluated via structural equation modeling (SEM), and the indirect relationships were tested via bootstrapping. Results: The results showed a direct and significant relationship between attachment to God and QoL (β=0.40, P=0.001), and between lifestyle and QoL (β=0.31, P=0.001). There was a negative relationship between attachment to God and depression (β=-0.40, P=0.001), in addition to QoL and depression (β=-0.37, P=0.001). The results of the indirect path analysis showed the mediating role of QoL in the relationship between attachment to God and lifestyle with depression (P=0.001). Conclusion: The results confirmed the proposed model's goodness of fit; therefore, this model can expand our understanding of the factors affecting depression in mothers of children with IDs to design preventive programs to mitigate their stress and depression.